A study on pregnancy outcome following previous spontaneous abortion: a hospital-based prospective observational comparative study - Singh, Priya; Gautam, Roli; Jeyaseelan, Shanti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Majority of spontaneous pregnancy loss occur in early gestation. Early pregnancy loss causes great physical and psychological distress to couples and creates apprehension in achieving future reproductive success. Previous abortions have a definite impact on the successful outcome of future pregnancies. Hence for such pregnancies careful antenatal care is mandatory. Careful surveillances required in pregnancies preceded by spontaneous abortions, for early detection of possible complications. Methods: This was a prospective observational comparative study conducted on 184 antenatal women (92 patients with previous spontaneous abortion, no full-term delivery, selected as cases while 92 patients with previous full term normal vaginal delivery with no previous abortion selected as control) attending antenatal OPD at Holy Family Hospital, New Delhi, from October 2020 to May 2022. All women received regular antenatal care and were followed up till delivery for maternal and foetal outcome. Results: For predicting pregnancy outcome following previous spontaneous abortion showed statistically significant in term of obesity, 56.52% patients were obese in cases while in controls only 48.91%. Duration of marriage, in cases is 2.22 years, where as in controls were 4.24 years with significant result. Interpregnancy interval (months) in cases was 10.58±4.19 whereas in controls it was 32.53±14.41 with significant result. Antenatal complications in term of GDM, hypothyroidism, IUGR more in cases than controls. Conclusions: We found that prior spontaneous abortion miscarriage is definitely a risk factor for the next pregnancy, making present pregnancy a high-risk pregnancy.